ANTHELMINTIC ACTIVITY OF PYROSTEGIA VENUSTA USING PHERETIMA POSTHUMA (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Approximately 3 million people are infected with helminthes worldwide. Helminthes infections are commonly found in villages of developing countries and are being recognized as cause of much acute as well as chronic illness among the human beings as well as cattle’s. Hence, the treatment for helmintic infection is of utmost need. The high cost of modern anthelmintics has limited the effective control of these parasites. However, increasing problems of development of resistance in helminthes against anthelmintics have led to the proposal of screening medicinal plants for their anthelmintic activity. Literature survey revealed that there are only few reports available on phytochemical and pharmacological studies of this plant. In the present investigation we have made a sincere attempt to evaluate the anthelmintic property of chloroform and methanol extracts of Pyrostegia venusta using Pheretima posthuma as an experimental helminthes model. Piperazine citrate was used as the standard reference. Five different concentrations (2.5, 5.0, 7.5, 10.0 and 12.5 mg/ml) of chloroform and methanol extracts were used to determine their effect as time taken to paralysis and time to induce death in the worms. Among the various concentrations of chloroform extract tested, 12.5 mg/ml showed efficient anthelmintic activity with paralysis time (23 min) and death time (44 min). Among all the concentrations of methanolic extract tested, 12.5 mg/ml showed significant results with paralysis time (34 min) and death time (78 min) respectively. This investigation revealed that chloroform extract was more effective in its anthelmintic action against Pheretima posthuma when compared to methanolic extract. But both the extracts were less potent when compared with standard drug piperazine citrate.